LPS-induced maternal inflammation promotes fetal leukocyte recruitment and prenatal organ infiltration in mice - Hudalla, Hannes; Karenberg, Katinka Patricia; Kuon, Ruben-Jeremias; Pöschl, Johannes; Tschada, Raphaela; Frommhold, David (Pediatric research, 2018)
A pro-inflammatory intrauterine milieu accounts for increased perinatal morbidity and mortality. We asked how maternal inflammation as seen in endotoxemia affects fetal leukocyte recruitment in vivo during late gestation. Inflammation was induced in pregnant LysEGFP-mice by intraperitoneal LPS injection between gestational day 14 and 18 (E14-E18). After 20 h, intravital fluorescence microscopy was performed on fetal yolk sac venules to examine leukocyte rolling (number of rolling cells/min) and adhesion (>30 s). Infiltration of neutrophils into chorion/amnion, lung, and kidney were quantified by immunofluorescence microscopy. At high doses (2 × 1 mg/kg), LPS triggered preterm birth (PTB) and intrauterine fetal death (IUFD), with early gestations at high risk of IUFD and late gestations prone to PTB. Lower LPS dosing (2 × 0.25 mg/kg) did not induce labor, but promoted maternal and fetal cytokine production, as well as neutrophilic infiltration of fetal membranes, as seen in chorioamnionitis (CAM). Baseline fetal leukocyte recruitment increased throughout gestation, and maternal inflammation further augmented adhesion at E16-E18. Enhanced leukocyte recruitment ultimately translated into prominent infiltration of fetal lung and kidney. LPS-induced maternal endotoxemia promotes IUFD, PTB, and fetal leukocyte recruitment depending on gestational age. Our proposed model may serve as a platform to test novel perinatal immune modulators.
Gesehen am 04.11.2019